Mapping between digital competencies and digitalization of the accounting profession among postgraduate accounting students / Yunita Awang ... [et al.] - Awang, Yunita; Taib, Azuraidah; Mohamed Shuhi, Shazalina; Zainal Zakaria, Zaiza Norsuriati; Ifada, Luluk Muhimatul; Sulistyowati, Sri (Universiti Teknologi MARA, 2023)
The Fourth Industrial Revolution has transformed global industrial demands and changed how people work, learn, communicate, access information, and spend their spare time. Similarly, the push towards digitalization of the accounting profession raised concerns about whether formal education and professional training will effectively equip accountants for the challenges brought on by the extensive use of IT in businesses and its dynamic nature. Thus, this study examined the relationship between digital competencies among postgraduate accounting students and the digitalization of the accounting profession. Questionnaires were distributed via online to postgraduate accounting students at a comprehensive university in Malaysia. Based on 136 responses, the results show that all four elements of digital competence have high mean scores. In addition, media literacy and information and communication technology literacy are insignificant, whereas information literacy and digital literacy are significant towards the digitalization of accounting profession. The results of this study can be used as a benchmark to evaluate the digital competencies of postgraduate accounting students who have some job experiences, as this may indicate how prepared the players are for the digitization of the accounting profession. Ultimately, this research might combine the efforts of university management and professional accounting bodies to get the players ready for the digitalized accounting profession. Future research may be conducted on postgraduate accounting students at other public and private universities and may also be expanded to assess non-accounting postgraduate students’ digital competencies towards digitalization in their related fields.